Mesenchymal stem cells suppress CD8+T cell-mediated activation by suppressing natural killer group 2, member D protein receptor expression and secretion of prostaglandin E2, indoleamine 2, 3-dioxygenase and transforming growth factor-β. (7th November 2014) - Li, Mingfen; Sun, Xuyong; Kuang, Xiaocong; Liao, Yan; Li, Haibin; Luo, Dianzhong
Summary: Bone marrow mesenchymal stem cells (BMSCs) inhibit immune cell responsiveness, and especially of T lymphocytes. We showed that BMSCs markedly inhibited the proliferation and cytokine production by CD8 + T cells by a cell-to-cell contact phenomenon and secretion of soluble factors. BMSCs down-regulate the expression of natural killer group 2, member D protein (NKG2D) receptors on CD8 + T cells when co-cultured with them. Moreover, CD8 + T cells that express low levels of NKG2D had impaired proliferation after triggering by a mitogen. The major histocompatibility complex (MHC) class I chain-related (MIC) A/B molecule, which is a typical ligand for NKG2D, was expressed on BMSCs, and caused dampening of cell proliferation. Monoclonal antibody blocking experiments targeted to MIC A/B impaired CD8 + T cell function, as evaluated by proliferation and cytokine production. In addition, the production of prostaglandin E2 (PGE2 ), indoleamine 2, 3-dioxygenase (IDO) and transforming growth factor (TGF)-β1 were increased when BMSCs were co-cultured with CD8 + T cells. The addition of specific inhibitors against PGE2, IDO and TGF-β partially restored the proliferation of CD8 + T cells. Our results suggest that BMSCs suppress CD8 + T cell-mediated activation by suppressing NKG2D expression and secretion of PGE2, IDO and TGF-β. Our observations further confirm the feasibility of BMSCs as a potential adoptive cellular therapy in immune-mediated diseases such as graft- versus -host disease (GVHD).